Association of H1-antihistamines with torsade de pointes: a pharmacovigilance study of the food and drug administration adverse event reporting system. Issue 1 (2nd January 2021) - Ali, Zahid; Ismail, Mohammad; Khan, Fahadullah; Sajid, Hira
ABSTRACT: Background : This study aimed to measure the association of various H1-antihistamines (H1A) with Torsade de Pointes (TdP), and present a comprehensive overview of H1A-induced TdP cases reported to the Food and Drug Administration Adverse Event Reporting System (FAERS). Methods : All H1A-induced TdP cases (n = 406) were retrieved from the FAERS database using the preferred term 'Torsade de Pointes' of MedDRA version-22 from 1990 to 2019. Four data-mining algorithms were used for disproportionality analysis: Reporting Odds Ratio (ROR); Proportional Reporting Ratio (PRR), Empirical Bayes Geometric Mean (EBGM), and Information Content (IC). H1A with >3 TdP cases were included. Results : A total of 12 signals (Astemizole, cetirizine, chlorpheniramine, clemastine, desloratadine, diphenhydramine, hydroxyzine, loratadine, meclizine, promethazine, terfenadine, and trimeprazine) were identified including six new signals (cetirizine, chlorpheniramine, clemastine, desloratadine, loratadine, and meclizine). The number of risk factors (p = 0.031) and concomitant QT-prolonging drugs (p = <0.001) were significantly lower among new signals vs old signals. Moreover, new signals were strongly associated with QT-prolongation, cardiac reactions, and electrolyte abnormalities as compared with old signals. Conclusions : Our study found the increased torsadogenic potential of new signals compared with previously known old signals, hence necessitating clinical studies to determine the actual torsadogenic potential of newly identified signals.